The importance of genetic counseling and screening for people with pathogenic SMARCE1 variants: A family study. Issue 2 (13th November 2020) - Shoakazemi, Alireza; Hewitt, Alan; Smith, Miriam J.; du Plessis, Daniel; Thomas, Owen; Stivaros, Stavros M.; Deniz, Kenan; Hammerbeck‐ward, Charlotte; Rutherford, Scott A.; King, Andrew Thomas; Evans, D. Gareth
Abstract: Clear cell meningioma (CCM) is a rare variant of meningioma. In recent years, an association between cranial and spinal CCMs and germline loss of function mutations in the SMARCE1 gene ( SWI/SNF chromatin remodeling complex subunit gene) has been discovered. We report a family with an incidental large spinal clear cell meningioma in a young adult following reflex screening for a germline loss of function pathogenic variant (PV) in the SMARCE1 gene. The index patient's mother and maternal grandfather were both also tested positive presymptomatically for SMARCE1 . His mother developed intracranial and spinal meningiomas and his maternal grandfather developed a spinal CCM 4 years following a clear spinal MRI scan which required surgical excision. In this report we particularly emphasize the importance of genetic counseling and screening in siblings, parents and offspring of patients who are diagnosed with intracranial or spinal CCM in the context of SMARCE1 PVs. We recommend brain and spine Imaging screening of asymptomatic SMARCE1 PV carriers at least every 3 years, even if the baseline scan did not show any tumors.